2012
DOI: 10.1126/scitranslmed.3004582
|View full text |Cite
|
Sign up to set email alerts
|

Immune Parameters Correlate with Protection Against Ebola Virus Infection in Rodents and Nonhuman Primates

Abstract: Ebola virus causes severe hemorrhagic fever in susceptible hosts. Currently, no licensed vaccines or treatments are available; however, several experimental vaccines have been successful in protecting rodents and nonhuman primates (NHPs) from the lethal Zaire ebolavirus (ZEBOV) infection. The objective of this study was to evaluate immune responses correlating with survival in these animals after lethal challenge with ZEBOV. Knockout mice with impaired ability to generate normal T and/or B cell responses were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
132
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 138 publications
(142 citation statements)
references
References 48 publications
10
132
0
Order By: Relevance
“…The strongest B cell responses were observed in animals receiving Ad-IFN and ZMAb starting at 3 dpi (Cyno72h and Rhesus72h groups) because IgG titers for these animals plateau by 14 dpi, compared to 28 dpi for the Cyno96h NHPs. High EBOV-specific IgG levels were shown to correlate with survival of lethally infected NHPs (21). An EBOV-GP-specific T cell response was observed at 21 dpi in both the IFN-g ELISpot and the intracellular cytokine flow cytometry assays.…”
Section: Discussionmentioning
confidence: 93%
“…The strongest B cell responses were observed in animals receiving Ad-IFN and ZMAb starting at 3 dpi (Cyno72h and Rhesus72h groups) because IgG titers for these animals plateau by 14 dpi, compared to 28 dpi for the Cyno96h NHPs. High EBOV-specific IgG levels were shown to correlate with survival of lethally infected NHPs (21). An EBOV-GP-specific T cell response was observed at 21 dpi in both the IFN-g ELISpot and the intracellular cytokine flow cytometry assays.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, Geisbert et al (12) showed rVSV/ZEBOV-GP vaccination failed to protect SHIV-infected macaques that failed to generate a ZEBOV-GP-specific IgG response following vaccination. More recently, a study by Wong et al (20) showed that an adenovirus-based vaccine failed to protect mice genetically deficient in B or CD4+ T cells, whereas mice lacking CD8+ T cells were completely protected. Additional analyses of vaccinated guinea pigs and cynomolgus macaques revealed statistically higher antibody titers in survivors compared with nonsurvivors (20).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, a study by Wong et al (20) showed that an adenovirus-based vaccine failed to protect mice genetically deficient in B or CD4+ T cells, whereas mice lacking CD8+ T cells were completely protected. Additional analyses of vaccinated guinea pigs and cynomolgus macaques revealed statistically higher antibody titers in survivors compared with nonsurvivors (20). These observations are in line with the results presented in this manuscript and strongly suggest that CD4+ T-cell help to B cells rather than CD4+ T-cell effector functions play a key role in protection.…”
Section: Discussionmentioning
confidence: 99%
“…T ese data support a greater relative importance of humoral as compared with cellular response for this vaccine (8). Recent studies suggest that innate responses may aid the humoral immune response in VSV-vectored vaccine-induced protection (6,9).…”
Section: Immunology Of Protection From Ebola Virus Infectionmentioning
confidence: 68%
“…Viral soluble glycoprotein (sGP), which is a nonstructural viral protein that shares features with GP and is secreted from infected cells, may inf uence (6). Moreover, NHP studies using VSVvectored vaccine reported protection from Ebola Zaire challenge in 4/4 animals, with antibody titer in the 1:100 to 1:1000 range (7).…”
Section: Immunity To Ebola Virusmentioning
confidence: 99%